P3.197 Uptake and Case Detection of Prenatal Screening of Maternal Syphilis, HIV and Hepatitis C, in British Columbia, Canada, 2007–2011. (13th July 2013) - Gilbert, M; Alvarez, M; Krajden, M; Buxton, J A; Lester, R; Money, D; Kuo, M; Ogilvie, G
Abstract : Background: In British Columbia (BC), Canada, (pop 4.6 million), prenatal screening for rubella, syphilis, and HIV is routinely recommended while hepatitis C (HCV) screening is based on risk criteria. We determined testing uptake and case detection rates at prenatal screening for these important perinatally transmissible pathogens. Methods: We identified prenatal specimens for women aged 16–45 years between 2007–11 from the BC Public Health Reference Microbiology Laboratory and calculated the proportion of unique women screened for rubella, syphilis, HIV, and HCV per calendar year. Records were linked to laboratory surveillance data, permitting inclusion of prior testing history for HIV and HCV, to determine if detected cases were newly diagnosed at screening (new diagnoses/100, 000) or a previously identified case. HIV and HCV prevalence were defined as all new and prior diagnoses among screened women (prevalence/100, 000). Results: Of the 233, 203 women who underwent one or more prenatal screening in the study period, 96.9% were screened for rubella, 93.3% for syphilis, 93.8% for HIV, and 21.5% for HCV. Over 5 years, syphilis, HIV, and HCV screening increased by 4.4%, 4.3%, and 8.3%, respectively. The overall syphilis diagnosis rate was 15.4/100, 000 and decreased over the study period. For HIV, the overall new diagnosis rate and prevalence was 5.1 and 45.9/100, 000 respectively; for HCV the corresponding values were 82.8 and 551.5/100, 000. The new diagnosis rates for HIV and HCV decreased over the study period while there were no significant changes in prevalence. Conclusion: In BC, prenatal screening for syphilis and HIV is high and improving annually with declining diagnosis rates. Previous research in BC suggests HCV prevalence in pregnant women in BC is underestimated based on risk-based screening. The low HCV screening rates and high prevalence observed in our study corroborates the need to consider broader prenatal HCV screening.